2018
DOI: 10.1186/s13054-017-1928-2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative fluid management in kidney transplantation: a black box

Abstract: The incidence of delayed graft function in patients undergoing kidney transplantation remains significant. Optimal fluid therapy has been shown to decrease delayed graft function after renal transplantation. Traditionally, the perioperative volume infusion regimen in this patient population has been guided by central venous pressure as an estimation of the patient’s volume status and mean arterial pressure, but this is based on sparse evidence from mostly retrospective observational studies. Excessive volume i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 77 publications
0
61
0
3
Order By: Relevance
“…The fundamental role of health care professionals involved in perioperative fluid management of kidney transplantation is to identify the perfect balance of fluid therapy. Accumulating evidence supports the concept that fluid therapy should be individualized and based on dynamic indices of the intravascular volume [10]. Dynamic variation in the arterial waveform-derived parameters systolic pressure variation (SPV), pulse pressure variation (PPV), and stroke volume variation (SVV) in mechanically ventilated patients are currently the most precise predictors of fluid responsiveness, particularly when compared to static parameters [10,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fundamental role of health care professionals involved in perioperative fluid management of kidney transplantation is to identify the perfect balance of fluid therapy. Accumulating evidence supports the concept that fluid therapy should be individualized and based on dynamic indices of the intravascular volume [10]. Dynamic variation in the arterial waveform-derived parameters systolic pressure variation (SPV), pulse pressure variation (PPV), and stroke volume variation (SVV) in mechanically ventilated patients are currently the most precise predictors of fluid responsiveness, particularly when compared to static parameters [10,32].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence supports the concept that fluid therapy should be individualized and based on dynamic indices of the intravascular volume [10]. Dynamic variation in the arterial waveform-derived parameters systolic pressure variation (SPV), pulse pressure variation (PPV), and stroke volume variation (SVV) in mechanically ventilated patients are currently the most precise predictors of fluid responsiveness, particularly when compared to static parameters [10,32]. This study revealed how the “tailored” approach, achieved through the implementation of PGDT strategies during kidney transplantation, might considerably decrease the incidence rate of major perioperative complications and increase the survival rate of the graft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of vascular autoregulation of the kidney transplant keeping the arterial blood pressure within physiological limits, this parameter gained increased attention during the last decade. 9,11 The mean arterial pressure (MAP) at the time of reperfusion is essential and should be kept higher than 80 mm Hg to avoid poor postoperative graft function. 8,11 It is still unclear which catecholamine to prefer.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Calixto Fernandes et al 14 suggested managing fluid therapy using a "flow-directed" model, where a positive response to 500 mL of crystalloid is defined as a 15% increase in cardiac output by noninvasive monitoring with a 2 mm Hg rise in CVP; however, this remains theoretical, and prospective studies are necessary. 14,26 Enhanced Recovery After Surgery. Halawa et al 27 described their experience implementing an enhanced recovery protocol for 286 kidney transplant recipients.…”
Section: Anesthetic Managementmentioning
confidence: 99%